The Implementation of IoT-Based Siwarola and Marketplace to Improve the Welfare of Farmers: Implementasi Siwarola Berbasis IoT dan Pasar Online untuk Meningkatkan Kesejahteraan Petani - Mawardi, Mawardi; Sihombing, Panangian Mahadi; Rafiqah Humaira (Universitas Lancang Kuning, 2025)
This activity aims to improve the welfare of freshwater fish farmers through the implementation of an aerator monitoring and control system (Siwarola) based on the Internet of Things (IoT) and online marketplace (Marketplace). Training and mentoring were carried out at the Pondok Miri Asri Farmer Group, Deli Serdang Regency, with pre-test and post-test evaluations as well as Likert scales. The training that has been provided includes socialization of water quality parameters suitable for freshwater fish farming, the application of IoT-based Siwarola technology, and Marketplace applications in the form of Tokopedia and Shopee. The results show that by applying IoT-based Siwarola, the average fish weight has increased by 109.52% and reduced the average tilapia mortality rate by 44.44%. Meanwhile, by jointly applying the Marketplace application and IoT-based Siwarola technology, it has succeeded in expanding marketing beyond the local area and increasing partner revenue by up to 190.98%. This program demonstrates the effectiveness of IoT-based technology and Marketplace applications in supporting sustainable fish farming results